1998
DOI: 10.1093/wber/12.1.29
|View full text |Cite
|
Sign up to set email alerts
|

A Panel Data Analysis of the Fungibility of Foreign Aid

Abstract: , seminar participants at the World Bank, and three anonymous referees. Vinaya Swaroop acknowledges financial assistance from the World Bank (research grant RPO 679-76).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
257
1
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(269 citation statements)
references
References 20 publications
5
257
1
6
Order By: Relevance
“…The fungibility of aid may undermine donor attempts to direct more funds to specific targets. However, aid for, say, basic education or rural infrastructure is unlikely to be fully fungible (Feyzioglu, Swaroop and Zhu 1998). 17 This is particularly true in countries heavily dependent on aid, where the large contribution of aid to public budgets 8 limits the discretion of local governments to shift resources.…”
Section: The Sectoral Allocation Of Aid: Some Stylized Factsmentioning
confidence: 99%
“…The fungibility of aid may undermine donor attempts to direct more funds to specific targets. However, aid for, say, basic education or rural infrastructure is unlikely to be fully fungible (Feyzioglu, Swaroop and Zhu 1998). 17 This is particularly true in countries heavily dependent on aid, where the large contribution of aid to public budgets 8 limits the discretion of local governments to shift resources.…”
Section: The Sectoral Allocation Of Aid: Some Stylized Factsmentioning
confidence: 99%
“…As Altincekic and Bearce (2014) argue, aid has never been as fungible as many scholars imply. They point out that the evidence about aid fungibility relies largely on a single paper (Feyzioglu et al 1998), which found high fungibility only in one sector: agriculture. Moreover, donors have grown less inclined over time to give aid as direct budget support, which is likely easier for elites to capture.…”
Section: Introductionmentioning
confidence: 99%
“…When confronted with a counterpart payment schedule, governments may decide to cut back on their own efforts and reduce projected budget allocations for mitigation-related spending. A certain degree of so-called 'fungibility' is innate to most aid instruments, but arguably more pronounced in the case of specifically targeted support, including debt swaps (see Feyzioglu et al, 1998). So, how does our case perform in terms of these two forms of additionality?…”
Section: Delivering More Resources For Climate Change Mitigationmentioning
confidence: 94%